The aesthetics of the sculptural formulations of swords in the Al-Kafeel Museum of Treasures and Manuscripts (Al-Academy, 2023)
The research included (the aesthetics of the sculptural formulations of swords in the Al-Kafeel Museum) four chapters. Al-Kafeel Museum.)Within the time period: (1240 AH / (1824 and 1825) AD - 1312 AH / (1894 and 1895) AD). The second: the types of Islamic swords. The third chapter included (research procedures), and the analysis of samples from the sample (3) as a model according to the descriptive approach, and the fourth chapter dealt with (results, conclusions, recommendations, and proposals). As well as recommendations, proposals and sources.